Clinical Application of Neuroplastic Brain Research in Eating Disorder Treatment - Abigail H. Natenshon (Open Access Journal of Science and Technology, 2018)
Eating disorders (ED) are disorders of the brain. As scientists acknowledge the genetic basis of ED and their deleterious impact on brain circuitry, practitioners need to recognize the importance of healing the eating disordered brain, along with the patient. The time has come for the ED treatment community to access the neuroplastic brain's capacity to heal itself through the introduction of non-invasive, integrative, adjunctive neurophysiological interventions into mainstream ED clinical practice. Eating disorder pathology marks the loss of the brain's capacity to integrate mind, brain and body, impacting the integrity of the core self. By re-defining the development of the self as an embodied, sensory-based processgrounded in kinesthetic experience, 21st century brain research and technology has substantively expanded the breadth and depth of effective treatment strategies for ED and their co-occurring conditions to include various forms of somatosensory interventions. Neurophysiological and psychophysiological treatment interventions, by carving new neuronal pathways and creating connectivity that augments brain circuitry, carry the potential to remediate body image and self-image distortions, reintegrating the fragmented eating disordered core self. To date, intentional partnering between therapist, ED patient, and neuroplastic brain has been rarely applied in the clinical milieu and minimally referenced in the treatment literature. By bringing current neuroplasticity research into frontline practice, ED practitioners not only bridge the research/practice gap, but redefine new directions for future ED research.